2017
DOI: 10.20960/nh.1111
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of body fat among 2-to-7-year-old Spanish children by different skinfolds equations and waist-to-height ratio

Abstract: Gutiérrez-Hervás A, Cortés-Castell E, Juste-Ruíz M, Gil-Guillén V, Rizo-Baeza MM. Estimation of body fat among 2-to-7-year-old Spanish children by different skinfolds equations and waist-to-height ratio. ResumenIntroducción: parece relevante analizar la composición corporal en la primera infancia. Sin embargo, en este rango de edad no existe un protocolo consensuado para determinar la composición corporal. Objetivo: determinar la fórmula más útil para estimar el porcentaje de grasa corporal contenido en niños… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…However, its use as an estimator of body fat percentage has been less studied in adults 37,42 and children 26 . In fact, most of the studies in children have rather been focused on body fat prediction 1821,23 in relatively small populations. In contrast, our study was conducted in a representative sample of the U.S. pediatric population aged 8 to 19 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its use as an estimator of body fat percentage has been less studied in adults 37,42 and children 26 . In fact, most of the studies in children have rather been focused on body fat prediction 1821,23 in relatively small populations. In contrast, our study was conducted in a representative sample of the U.S. pediatric population aged 8 to 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Height/waist ratio is the reciprocal of the widely used waist-to-height ratio (WHtR). Previous studies have shown that WHtR has a good linear relationship with BMI Z-scores in both girls and boys 2 to 7 years of age 18 . However, it appears that the association of body fat percentage with WHtR is not stronger than that with BMI in this population 1921 .…”
Section: Introductionmentioning
confidence: 90%